2011
DOI: 10.1016/j.jcrs.2011.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the surgically induced refractive effect of intrastromal corneal ring segments in keratoconus with standardized incision site and segment size

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…Preoperative and postoperative refractions with corrected visual acuities, keratometric data, refractive surgical effect, keratometric surgical effect, anterior elevation, keratometric axial, and keratometric axial difference maps. 1 The principal aim of the present study, therefore, was to determine whether the previously observed effect of two 0.3 mm ICRS (ie, flattening of the meridian orthogonal to the incision site and steepening in the meridian of the incision) was dependent on the location of the incision. This was assessed by measuring the refractive surgical effect and keratometric surgical effect of ICRS inserted at different relationships between the incision site and the keratometric steep meridian.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Preoperative and postoperative refractions with corrected visual acuities, keratometric data, refractive surgical effect, keratometric surgical effect, anterior elevation, keratometric axial, and keratometric axial difference maps. 1 The principal aim of the present study, therefore, was to determine whether the previously observed effect of two 0.3 mm ICRS (ie, flattening of the meridian orthogonal to the incision site and steepening in the meridian of the incision) was dependent on the location of the incision. This was assessed by measuring the refractive surgical effect and keratometric surgical effect of ICRS inserted at different relationships between the incision site and the keratometric steep meridian.…”
Section: Discussionmentioning
confidence: 95%
“…1 The incision site was placed at 90 degrees or according to the manufacturer's recommended nomogram. A After intraoperative ultrasonic pachymetry was performed at the incision site, a calibrated diamond knife was set at 70% to 80% of the mean measured corneal thickness and a 1.8 mm to 2.0 mm radial incision was made 7.0 mm from the optical zone.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tu et al 19 implanted symmetrical segments of the same thickness in a sample of keratoconus patients with different grades of the disease. They reported that the refractive and keratometric surgical effect of ICRS appeared to be positively associated with the stage of keratoconus; that is, the effect was greater the more advanced the keratoconus stage.…”
Section: Discussionmentioning
confidence: 99%
“…At the early stage, vision is usually correctable by spectacles or contact lens. Semi-circular plastic inserts as intrastromal corneal ring segments help reduce astigmatism [27,28]. However, cornea transplantation is required for severe and progressive keratoconus, which is Molecular Genetics of Keratoconus: Clinical Implications DOI: http://dx.doi.org/10.5772/intechopen.90623 a major cause for cornea transplantations in many countries [29].…”
Section: Timely Diagnosis For Treatmentmentioning
confidence: 99%